Interaction of Sirtuin 1 (SIRT1) candidate longevity gene and particulate matter (PM2.5) on all-cause mortality: a longitudinal cohort study in China - Yao Yao; Linxin Liu; Guang Guo; Yi Zeng; John S. Ji (BMC, 2021)
Abstract Background The SIRT1 gene was associated with the lifespan in several organisms through inflammatory and oxidative stress pathways. Long-term air particulate matter (PM) is detrimental to health through the same pathways. Methods We used the Chinese Longitudinal Healthy Longevity Survey (CLHLS) to investigate whether there is a gene-environment (G × E) interaction of SIRT1 and air pollution on mortality in an older cohort in China. Among 7083 participants with a mean age of 81.1 years, we genotyped nine SIRT1 alleles for each participant and assessed PM2.5 concentration using 3-year average concentrations around each participant's residence. We used Cox-proportional hazards models to estimate the independent and joint effects of SIRT1 polymorphisms and PM2.5 exposure on all-cause mortality, adjusting for a set of confounders. Results There were 2843 deaths over 42,852 person-years. The mortality hazard ratio (HR) and 95% confidence interval (CI) for each 10 μg/m3 increase in PM2·5 was 1.08 (1.05-1.11); for SIRT1_391 was 0.77 (0.61, 0.98) in the recessive model after adjustment. In stratified analyses, participants carrying two SIRT1_391 minor alleles had a significantly higher HR for each 10 μg/m3 increase in PM2.5 than those carrying zero minor alleles (1.323 (95% CI: 1.088, 1.610) vs. 1.062 (1.028, 1.096) p for interaction = 0.03). Moreover, the interaction of SIRT1 and air pollution on mortality is significant among women but not among men. We did not see significant relationships for SIRT1_366, SIRT1_773, and SIRT1_720. Conclusion We found a gene-environment interaction of SIRT1 and air pollution on mortality, future experimental studies are warranted to depict the mechanism observed in this study.